Excretory over-expression of Bacillus sp. G1 cyclodextrin glucanotransferase (CGTase) in Escherichia coli: Optimization of the cultivation conditions by response surface methodology - Lo, Po Kim; Hassan, Osman; Ahmad, Arshad; Mahadi, Nor Muhammad; Illias, Rosli Md (Elsevier Inc., 2007)

(untitled)
Co-expression of cyclodextrin glucanotransferase (CGTase) from Bacillus sp. G1 (cgt) with bacteriocin release protein (BRP) in Escherichia coli system resulted in the expression and excretion of the enzyme into the culture medium. The cultivation conditions were then optimized with the objective to enhance the production of extracellular recombinant CGTase using response surface methodology (RSM) that based on rotatable central composite design (CCD). The process consisted of a total of 50 experiments involving 10 star points and 8 replicates at the central points. The optimum predicted cultivation conditions for the maximum expression of extracellular recombinant CGTase were found to be comprised of: 20 Â°C post-induction temperature, induction-starting time when cell optical density is 0.3 at 600 nm, 1.0 mM xylose, 50 Î¼M IPTG and 29 h post-induction time, with a predicted extracellular recombinant CGTase activity of 9144.28 U/ml. The experimental extracellular recombinant CGTase activity obtained was 9542.30 U/ml, which was very close to the predicted value. The expression of extracellular recombinant CGTase improved about 151-fold after the optimization was conducted.